A Modern Comparison of Urodynamic Findings in Diabetic Versus Nondiabetic Women. Issue 1 (January 2020) - Malik, Rena D.; Cohn, Joshua A.; Volsky, Jessica; Garvey, Sarah; Chang, Charles; Bales, Gregory T.; Chung, Doreen E.
Abstract : Objectives: Few contemporary studies exist regarding urodynamic (UDS) findings in patients with diabetes mellitus (DM), and data are conflicting. Our aim was to compare UDS findings in women with and without DM. Methods: Data from female patients in a prospectively maintained UDS database (2010–2014) were reviewed. Studies were performed according to International Continence Society standards. Clinical data, presenting symptoms, and UDS findings were compared in women with and without DM, controlling for demographic and pertinent variables. Results: There were 384 patients who met the inclusion criteria, of whom 88 (26%) had DM. Symptoms at presentation were not statistically different in women with and without DM. Women with DM had larger bladder capacity (mean, 493 mL vs 409 mL; P = 0.005) and had more detrusor underactivity (30% vs 18%, P = 0.042) when compared with nondiabetic women. Diabetic women were more frequently diagnosed as having impaired sensation, or lack of desire to void, at 75% of capacity (17% vs 5%, P = 0.001). In women with diabetes, a serum hemoglobin A1c level of at least 7.5% was associated with delayed first sensation and first urge. Diagnosis of DM of more than 10 years was associated with greater volume at first urge, and maximal capacity, lower detrusor pressures, and higher postvoid residual. Conclusions: In this contemporary series, women with DM demonstrated similar presenting complaints to women without DM but had significantly altered UDS findings. Among diabetic female patients, diabetes control and duration of diabetes seem to impact bladder sensation and contractility. Urodynamics may be helpful in diabetic female patients to diagnose underlying concealed bladder dysfunction before initiation of treatment.